Optimizing Return-to-Office Strategies With Organizational Network Analysis - Cross, Rob; Cross, Rob; Gray, Peter (MIT Sloan Management Review, 2021)
Leaders will need to offer a compelling rationale for why post-pandemic work models that include some degree of in-person collaboration are not only good for the company but also valuable for employees. The authors explain how organizational network analysis -- a methodology that maps employees' working relationships -- can help guide leaders' return-to-office decisions and show employees how hybrid work can improve their own effectiveness.